Kaum Milenial & Kebudayaan Nias: Di Persimpangan Jalan - Tuhoni Telaumbanua (SUNDERMANN: Jurnal Ilmiah Teologi, Pendidikan, Sains, Humaniora dan Kebudayaan, 2019)
This article is intended to explicate how to assist the millennial generation of Ono Niha not to be uprooted from the Nias identity amid globalization and encourage them to participate in preserving Niasan culture. Through the social-historical analysis, this article appeals to the millennial generation not to be alienated from their own culture but participate in cultural conservation. Therefore, it is crucial to conduct a dialogue with millennials by presenting their origins, strengthening the family as a cultural home. Through formal education, the young generation is educated to recognize their cultural values and local wisdom as cultural heritage. Empowering them as subjects and objects of culture is one of the practices to understand local wisdom in the context of Nias. Moreover, increasing institutional roles in preserving various cultural elements are part of the way to increase the interest of millennial to learn their existence, identity, and culture.